THE INSTRUCTION TO OVERCOME THE INERT KNOWLEDGE ISSUE IN SOLVING MATHEMATICAL PROBLEM - Febrian Febrian (Jurnal Gantang, 2016)
One characteristic of typical mathematical problem is that it requires bunch of relevant prior knowledge. This knowledge is built consecutively and is recalled whenever needed to promote student to solve the problem. The process undertaken by the solver to utilize existing relevant prior knowledge while solving the problem is called access. However, this access is possible subject to disturbance for some reasons. This literature study addresses some factors that can distract access: factor related to metaprocess and factor related to deficit structure. The variants included in both factors have been proved through research as the contributors of the accessibility of relevant prior knowledge. Knowledge that cannot be accessed is called inert knowledge, the main reason for why solver face the difficulty to find the answer to given mathematical problem. The explanation leads to the suggestion of how to tackle the inertia of particular knowledge. One of them are through the instruction setting. Realistic Mathematics Education as one of approaches in learning can be a possible alternative for the issue of inert knowledge. Keywords. Mathematical problem solving, prior knowledge, access, inert knowledge, Realistic Mathematics Education